PENERAPAN STRATEGISEPAK BOLA VERBAL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 16 PADANGTAHUN PELAJARAN 2013/2014 - Fahmi, Septia Vramita; Zulfaneti, Zulfaneti; Melisa, Melisa (STKIP PGRI Sumbar, 2013)
Based on background knowledge of this research was understanding of concept mathematics at VIII grade of SMP N16 Padang. It is caused by the materials that students have been lost from their mind. This research is to determine whether studentsâ understanding of concept mathematics by using Sepak Bola Verbal strategy better than studentsâ understanding of concept mathematics by using conventional strategy andto know how the students motivation ini learning by using sepak bola verbal strategy at VIII SMP N 16 Padang.Type of this research was experiment. Population of this research was students at VIII SMP N 16 Padang, and sample of this research was students class VIII.8as experimental class and VIII.6 as control class. Post-Test was as instrumentation in this research, with reliability 0.84.From the data analysis get mean score from studentsâ achievement in experimental class was 68.89 that high rather than in control class that was 57.04.Data analysis was done by using minitab program.P-value= 0.026so hypothesis use acceptable. So, we can conclude that studentsâ understanding of concept mathematics that used Sepak Bola Verbal strategy better than conventional strategy at VIII Grade of SMP N 16 Padang.